2017
DOI: 10.1080/02755947.2017.1307291
|View full text |Cite
|
Sign up to set email alerts
|

Implanting 8‐mm Passive Integrated Transponder Tags into Small Brook Trout: Effects on Growth and Survival in the Laboratory

Abstract: Passive integrated transponder (PIT) tags are commonly used to investigate relationships between individual fish and their environment. The recent availability of smaller tags has provided the opportunity to tag smaller fish. In this study, we implanted 8‐mm PIT tags into small Brook Trout Salvelinus fontinalis (35–50 mm FL; 0.35–1.266 g) and compared tag retention, growth rates, and survival of PIT‐tagged fish with those of fish subjected to handling only or to handling plus fin clipping. We also examined how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The 56% detection rate of Mottled Sculpin with 8mm PIT tags was higher than we had anticipated and was comparable to the capture probability of individual fish in single-pass backpack electrofishing, as reported for the Brook Trout Salvelinus fontinalis (57%; Letcher et al 2015), Mottled Sculpin (54%), Central Stoneroller Campostoma anomalum (54%), Creek Chub (55%), Brown Trout (59%), and Longnose Dace Rhinichthys cataractae (56%; Hense et al 2010). Use of 8-mm tags allows for the tagging of fish as small as 35-40 mm TL (Bangs et al 2013;Cary et al 2017;O'Donnell and Letcher 2017. Thus, the researcher is faced with a trade-off between higher detection efficiency but larger minimum fish size when using 12-mm tags versus lower detection efficiency but smaller minimum fish size when using 8-mm tags.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 56% detection rate of Mottled Sculpin with 8mm PIT tags was higher than we had anticipated and was comparable to the capture probability of individual fish in single-pass backpack electrofishing, as reported for the Brook Trout Salvelinus fontinalis (57%; Letcher et al 2015), Mottled Sculpin (54%), Central Stoneroller Campostoma anomalum (54%), Creek Chub (55%), Brown Trout (59%), and Longnose Dace Rhinichthys cataractae (56%; Hense et al 2010). Use of 8-mm tags allows for the tagging of fish as small as 35-40 mm TL (Bangs et al 2013;Cary et al 2017;O'Donnell and Letcher 2017. Thus, the researcher is faced with a trade-off between higher detection efficiency but larger minimum fish size when using 12-mm tags versus lower detection efficiency but smaller minimum fish size when using 8-mm tags.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected on uniquely marked individuals are useful for obtaining information on life history and biology (Ruetz et al 2006). Among marking techniques, PIT tags are commonly used in fisheries research because they are small in size and are relatively inexpensive Banish et al 2016;Cary et al 2017;O'Donnell and Letcher 2017). Passive integrated transponder technology has multiple applications in mark-redetection studies.…”
mentioning
confidence: 99%
“…; Tiffan et al. ) and as small as 35 mm FL (O'Donnell and Letcher ). Several studies have indicated that juveniles and small‐bodied species (<100 mm TL) belonging to several families, including Cyprinidae, Cottidae, Lotidae, and Percidae, can also be PIT‐tagged with no adverse effects (Baras et al.…”
mentioning
confidence: 99%
“…However, developments in PIT technology have led to smaller tags, meaning that smaller‐bodied species may now be studied using this method (Roussel et al. ; O'Donnell and Letcher ). The small size, low cost, and long lifetime of PIT tags are major factors in their popularity and wide application in fisheries management.…”
mentioning
confidence: 99%
See 1 more Smart Citation